Performance management routines that work? an early assessment of the GPRA modernization act - Moynihan, Donald P.; Kroll, Alexander (2016)
The Government Performance and Results Act (GPRA) of 1993 provided a well-studied framework for U.S. federal performance management initiatives. In the aftermath of the update of GPRA in 2010 with the GPRA Modernization Act, the authors offer the first systematic scholarly assessment of the new legislation. Managerial use of performance data was an explicit goal of the Modernization Act, an objective that eluded prior federal reforms. The Modernization Act established a new series of performance routines to encourage performance information use. The analysis shows that as federal managers experience those routines, they are more likely to report using performance data to make decisions. Specifically, routines centered on the pursuit of cross-agency priority goals, the prioritization of a small number of agency goals, and data-driven reviews are all associated with higher rates of performance information use. The authors also find that managers in better-run data-driven reviews report greater use of performance data. - Reproduced.
Keywords: Performance appraisal